2020
DOI: 10.21203/rs.2.24493/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparing Clinical Outcomes of Piperacillin-Tazobactam Administration and Dosage Strategies in Critically Ill Adult Patients: A Systematic Review and Meta-Analysis

Abstract: Background: Recently, continuous administration of piperacillin-tazobactam has been proposed as a valuable alternative to traditional intermittent administration especially in critically ill patients. However, antibiotic dosing remains a challenge for clinicians as antibiotic dosing regimens are usually determined in non-critically ill hospitalized adult patients. The aim was to conduct a systematic review to identify and highlight studies comparing clinical outcomes of piperacillin tazobactam dosing regimens,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…independently using the 9-star Newcastle-Ottawa Scale (NOS) and the randomized controlled trials using the Cochrane collaboration risk of bias tool [17]. The evaluation features random sequence generation, allocation concealment, blinding of the outcome assessment, blinding of subjects and personnel, analysis of selective reporting, incomplete outcome data, and other biases [18]. Each item was evaluated by 2 independent reviewers (H.D.N.…”
Section: Methodsmentioning
confidence: 99%
“…independently using the 9-star Newcastle-Ottawa Scale (NOS) and the randomized controlled trials using the Cochrane collaboration risk of bias tool [17]. The evaluation features random sequence generation, allocation concealment, blinding of the outcome assessment, blinding of subjects and personnel, analysis of selective reporting, incomplete outcome data, and other biases [18]. Each item was evaluated by 2 independent reviewers (H.D.N.…”
Section: Methodsmentioning
confidence: 99%
“…To maximize therapeutic effect and for early reduction of bacterial burden, on the one hand it is important to consider starting treatment with a high dose of an antibiotic to achieve high drug concentrations as soon as possible [60]. On the other hand, several studies showed that continuous infusions (over 24 h) or prolonged infusions (over ≥3 h) of β-lactam antibiotics lead to better PK/PD targets attainment rates and patient outcomes than intermittent intravenous bolus administration (over 30-60 min, 1 to 6 times per day), particularly in critically ill patients and in patients with serious infections [61][62][63][64][65]. Administering β-lactams continuously or by prolonged infusion to achieve optimal PK/PD might slow the development of resistance and improve the outcomes of patients with sepsis and septic shock.…”
Section: Choose the Right Antibiotic Dosage And Route Of Administrationmentioning
confidence: 99%